Paradoxos da inclusão no trabalho: um estudo com pessoas com deficiência no setor público - Marques, Davi Sampaio (2018)
This paper aims to understand the perceptions of people with disabilities working in the public sector about their inclusion processes in their work environments. The process and practice of inclusion involves tensions that can be seen through the lens of paradox, which Ferdman (2017) divided into three categories: self-expression and identity, which involve the tensions between singularity and belonging; boundaries and standards, which may be stable or unstable; and safety and comfort, which can provide comfort or discomfort feelings that generate changes in themselves, in relationships and in the work environment. Any organization that seeks to adopt inclusive practices will encounter tensions involving each of these inclusion categories. Based on this theory, a qualitative, exploratory and descriptive field research was carried out, with semi-structured interviews being carried out with twelve people with disabilities who work as servants of a federal public university. The analysis and treatment of the data was performed through content analysis and with the aid of Atlas.ti software. Among the results, it was found that the phenomenon of inclusion is complex and multifaceted, being associated with tensions, failures and barriers, such as the presence of prejudice and discrimination in the work environments of the University. It has also been realized that feeling similar to others in some way seems to be more valued than feeling distinct, and that bureaucracy appears as a great barrier to the expansion of their borders, affecting their feelings of inclusion. Positive aspects related to the inclusion of PwD were also observed, such as: the desire for change, being the protagonists in this process; new professional practices of public management that seem to be being adopted in the University; and a high degree of awareness and knowledge of their causes among all interviewees. Among the contributions of the study are the theoretical developments on the subject of inclusion and, more specifically, people with disabilities, due to the fact that this research allows their voices to gain also the spaces of the academy and the production of knowledge. The paper also presents information that can serve as a basis for actions related to the management of inclusion in Universities and other public institutions or private companies.